Perancangan Alat Uji Tarik Universal Statis dengan Penggerak Servomotor Berkapasitas Maksimum 1 kN - Parulian Malau; Rakhmad Arief Siregar; M. Yusuf Rahmansyah Siahaan (Universitas Medan Area, 2022)
In this paper, the author discusses the process of designing static universal tensile test equipment suitable for the laboratory scale of the material. The design presents data on customer expectations and embodiment analysis of the design of the tensile testing machine. This study aims to design a tensile testing machine, choose a match in making a tensile testing machine design following customer expectations, and analyze the embodiment of the design of the tensile testing machine. This research uses quantitative methods using surveys or questionnaires distributed to the research sub-project. The results of this tensile testing machine questionnaire survey are processed into research data which translates into engineering needs and its development into the tool design concept. The result of this study is the design and specifications of the tensile testing machine with a servomotor drive. The tensile testing machine has been successfully designed and works well and has met customers' needs.